Komuniti minoriti dan pembentukan landskap politik lokal: penglibatan politik belia Siam di Semenanjung Malaysia - Gill, Sarjit Singh; Harun, Mohd Razali; Talib, Ahmad Tarmizi (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2014)
Minority political communities may indeed exert a crucial influence on both political landscapes and political outcomes. The present article discusses political involvement of minority Siamese youth in Peninsular Malaysia. The political discourse in Malaysia still continues to revolve exclusively within the ambits of the majority political community whereas political discussion of the minority community almost seems to be sidelined. In reality, the minority community also contributes to the political development of the nation. Following the 12th General Election (GE 12), the minority youths especially from amongst the Siamese community, are viewed as an important group in determining the political landscape, particularly during the 13th General Elections (GE 13). This is especially true in those states where there is a strong presence of the Siamese community, such as Kedah, Kelantan and Perlis. As observed, in the 12th General Elections, the ruling Barisan Nasional had lost in Kedah and failed to regain Kelantan which has the highest population of Siamese community in Malaysia. However, Kedah recapitulated into the hands of BN in the GE 13, while Kelantan continued to remain under the control of the Pakatan Rakyat (PR). This might demonstrate that the community's involvement in the elections was pivotal in bringing about political change. As such, a number of questions need to be examined, namely: Do youth from the Siamese community join political parties? What posts do they hold? Are they involved in political programs? What is certain is that their direct involvement in politics has the potential of impacting on political development, particularly on general elections.